Komunikasi Partisipatif Dalam Meningkatkan Literasi Digital Kebencanaan di Desa Tarahan Kecamatan Katibung Kabupaten Lampung Selatan - Akbar, Muhammad Fikri; Yuliani, Hafri; Suryanti, Poppy; Laras Ati, Henny Dewi; Damayati (Prosiding Seminar Nasional Pendidikan, Ilmu-Ilmu Sosial, dan Hukum (SENPISHUM), 2026)
This study aims to examine the role of participatory communication in enhancing disaster-related digital literacy in Tarahan Village, Katibung District, South Lampung Regency. The research was motivated by the low level of community understanding regarding the use of digital technology for disaster mitigation, despite the area’s high tsunami risk. A qualitative descriptive approach was employed, using data collection techniques such as participatory observation, in-depth interviews, and document analysis of the Indonesia Disaster Resilience Initiatives Project (IDRIP) socialization activities. The findings reveal that participatory communication significantly increased community engagement, with 70% of participants actively involved in discussions and decision-making. Disaster-related digital literacy also improved, rising from 20% before socialization to 65% afterward, supported by demonstrations of early warning applications and the establishment of a village WhatsApp group. Identified challenges included limited technological resources, passive participation, insufficient gender representation, and scheduling conflicts with village agendas. Solutions implemented included rescheduling activities, providing participant mentoring, requesting technological equipment, and utilizing local media. This study concludes that integrating participatory communication with digital literacy is an effective strategy for building community resilience to disasters. Recommendations include strengthening digital literacy training and developing community-based communication models to ensure the sustainability of disaster mitigation programs.